KEPASTIAN HUKUM PEMBATALAN SERTIFIKAT HAK MILIK AKIBAT CACAT ADMINISTRATIF - dedi sugiyanto (Jurnal Hukum Lex Generalis, 2024)
law Number 5 of 1960 concerning Agrarian Principles has provided a legal basis for both the government in its duties as the implementer of laws and regulations and for individuals or legal entities who wish to obtain legality in the form of land certificates as proof of ownership of a plot of land must carry out the land registration process. The process of issuing land rights must be based on physical data and legal data that can be legally accounted for. An administratively inaccurate certificate is one type of certificate that is problematic due to administrative defects, so an administratively inaccurate certificate can be submitted for cancellation of the certificate by a party who feels that their rights have been harmed due to the issuance of an administratively defective certificate. The formulation of the first problem in this study is How is the legal basis for the cancellation of a certificate of ownership due to administrative defects and how is the legal certainty of the cancellation of a certificate of ownership due to administrative defects. This study uses a Juridical-Normative research type because the problem will be analyzed by reviewing the laws and regulations related to Law Number 5 of 1960 concerning Agrarian Principles, Government Regulation Number 24 of 1997 concerning Land Registration, Government Regulation of the Republic of Indonesia Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases. The results of the study are that the legal provisions as the basis for the cancellation of land rights, namely the Certificate of Ownership Rights, are Law No. 5 of 1960 concerning Basic Regulations on Agrarian Principles, Government Regulation No. 24 of 1997 concerning Land Registration, Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units, and Land Registration, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 21 of 2020 concerning Handling and Settlement of Land Cases and Normatively overlapping regulations on the cancellation of Land Ownership Certificates create legal uncertainty for parties who are harmed due to the issuance or ratification of Land Ownership Certificates that are suspected or known to have administrative data defects such as physical data defects and legal data defects so that there is a need for regulatory codification that provides clear and firm rules regarding the cancellation of Land Ownership Certificates due to administrative defects and there is a need for good system integration in land rights registration as a manifestation of the general principles of good governance and normative sanctions for officials who are involved intentionally knowing that the application for issuance of land ownership certificates has administrative and legal defects but is still issued, normative sanctions regulations function as preventive measures so that officials or government officials do not abuse their authority (abuse of power).